A look at teaching skills: Challenges and complexities in Costa Rican education (Research, Society and Development, 2025)
Education is a constantly evolving social process; those engaged in teaching face challenges that go beyond the pedagogical realm. In this context, educational work is influenced by the synergies of an educational system while also being impacted by external factors that interact with internal elements, exacerbating imbalances and disrupting the smooth development of the classroom environment intended for student learning. This article aims to present a reflection on the complexities of the Costa Rican educational system that overload the teaching staff and demonstrate their resistance to an often-oppressive system. Concrete experiences and a critical analysis of Costa Rican education enrich this reflection. Therefore, the article addresses various situations that arise in the educational environment, revealing part of the reality experienced by those of us immersed in the system as we strive to deliver quality teaching that aligns with students' needs and society's demands.